Bacterial pneumonia score to identify bacterial pneumonia - Ied Imilda; Finny Fitry Yani; Didik Hariyanto; Darfioes Basir (Paediatrica Indonesiana, 2015)
Background Pneumonia is caused by either bacterial or viral etiologies, with similar symptoms in children. The bacterial pneumonia score (BPS) is a clinical assessment comprised of several investigations: age, assessment of axillary temperature, absolute neutrophil count, band neutrophil percentage, and interpretation of radiological examination. The score will use to differentiate the etiology of pneumonia. Objective To determine the sensitivity, specificity, positive predictive value, and negative predictive value of BPS in identifying bacterial pneumonia in children. Methods This diagnostic study was performed at Dr. M. Djamil Hospital, Padang, West Sumatera where subjects were selected by consecutive sampling. Fifty-seven patients were diagnosed with pneumonia. Three patients suffered from ventricular septal defects, 8 patients refused to provide blood specimens and 3 patients’ chest X-rays could not be interpreted, hence, 43 subjects were included in the study. Chest X-rays were interpreted by a pediatric pulmonology consultant. Leukocyte and differential counts were performed by a clinical pathology consultant. Subjects’ BPS scores were compared to multiplex PCR examinations of blood specimens, as the gold standard.